2013
DOI: 10.1371/journal.pone.0062863
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Effect of MARCKS Phosphorylation by Activated PKC: The Dephosphorylation of Its Serine 25 in Chick Neuroblasts

Abstract: MARCKS (Myristoylated Alanine-Rich C Kinase Substrate) is a peripheral membrane protein, especially abundant in the nervous system, and functionally related to actin organization and Ca-calmodulin regulation depending on its phosphorylation by PKC. However, MARCKS is susceptible to be phosphorylated by several different kinases and the possible interactions between these phosphorylations have not been fully studied in intact cells. In differentiating neuroblasts, as well as some neurons, there is at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…Figure 5A reveals that despite an increase in total MARCKS (Figure 3B), the amount of P-MARCKS decreased 1.8-fold as MKs maturated and proplatelets were formed ( Figure 5A), suggesting that MARCKS phosphorylation may be detrimental to proplatelet formation. Because PMA is a potent PKC activator that leads to specific and preferential MARCKS phosphorylation, 37,38 we used it to induce MARCKS phosphorylation (schematic in Figure 5B). Treatment of MKs with PMA significantly, dose-dependently decreased the number of proplatelet-producing MKs but increased the amount of P-MARCKS ( Figure 5C).…”
Section: Marcks Phosphorylation Inhibits Proplatelet Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5A reveals that despite an increase in total MARCKS (Figure 3B), the amount of P-MARCKS decreased 1.8-fold as MKs maturated and proplatelets were formed ( Figure 5A), suggesting that MARCKS phosphorylation may be detrimental to proplatelet formation. Because PMA is a potent PKC activator that leads to specific and preferential MARCKS phosphorylation, 37,38 we used it to induce MARCKS phosphorylation (schematic in Figure 5B). Treatment of MKs with PMA significantly, dose-dependently decreased the number of proplatelet-producing MKs but increased the amount of P-MARCKS ( Figure 5C).…”
Section: Marcks Phosphorylation Inhibits Proplatelet Formationmentioning
confidence: 99%
“…PP2A has been shown to be the main phosphatase responsible for MARCKS dephosphorylation. 20,38,39 Therefore, we treated MKs with the specific PP2A activator C2 ceramide and PP2A inhibitor okadaic acid ( Figure 5B). Consistent with our model where MARCKS dephosphorylation is necessary for proplatelet formation, C2 ceramide significantly enhanced proplatelet formation, whereas okadaic acid significantly inhibited proplatelet formation ( Figure 5D).…”
Section: Marcks Phosphorylation Inhibits Proplatelet Formationmentioning
confidence: 99%
“…This domain is only phosphorylated in neurons, does not affect association with membranes, and is yet to be functionally characterized (Tinoco et al, 2014 ). Interestingly, MARCKS has been demonstrated to cluster in groups with comparable phosphorylation states at the mutually exclusive S25 and ED residues (Toledo et al, 2013 ), perhaps due to the localization patterns induced by these modifications. The functional significance of phosphorylation outside of the ED requires further investigation; presently the vast majority of what is known regarding the regulation of MARCKS is in relation to phosphorylation by PKC.…”
mentioning
confidence: 99%
“…When protein sequences and their alignments are analyzed in more detail, we can see that, as it has been described for higher vertebrates alone (Li and Aderem, ; Blackshear, ), the three MARCKS conserved domains can still be recognized. Regarding the MH2, it is interesting that all nonteleost MARCKS and all teleost MARCKSA sequences share the presence of a serine phosphorylatable by Cdk5, homolog to chick S25, whose phosphorylation was previously shown to correlate to neuronal differentiation in chick and mouse embryos (Zolessi et al., ; Toledo et al., ; Contreras‐Vallejos et al., ). This serine is not present in any of the identified teleosts MARCKSB protein sequences, or in most MARCKSL1.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the MH2 domain appears as the most puzzling, as no function could yet be ascribed to it. Our group has demonstrated that it contains an extremely conserved serine residue, S25, which in the chick embryo is phosphorylated by Cdk5 in neuroblasts, some neurons, and some migrating neural crest cells, and this phosphorylation depends on the integrity of the actin cytoskeleton and on cell‐to‐cell adhesion (Zolessi and Arruti, ; Zolessi et al., ; Toledo and Arruti, ; Ruiz‐Perera et al., ; Toledo et al., ).…”
mentioning
confidence: 99%